A retrospective study of ultrasound-guided intervention for frozen shoulder in the frozen stage - Guan, Haitao; Wu, Qinfeng; Zhou, Yuan; Fan, Xing; Zheng, Kun; Si, Tong; Zhao, Jinli (Frontiers in Surgery, 2022)
Background: To investigate the clinical value of ultrasound (US)-guided intervention for frozen shoulder (FS) in the frozen stage. Methods: This study included 40 patients who had primary FS in the frozen stage and were evaluated by US. These 40 patients have all received conservative treatment elsewhere, and no satisfactory results have been achieved, with no improvement in active and passive movement angles, and no improvement in scores within 3 months. Therefore, their previous treatment was set as comparison. All patients underwent US-guided shoulder joint capsule distension by injection of sterilized water. Of these participants, 22 patients with scapulohumeral periarthritis received a compound betamethasone injection, and 14 patients with thickened coracohumeral ligaments (CHLs) underwent acupotomy lysis, and the remaining 4 patients had no extra treatments. The Constant-Murley score (CMS) was evaluated before and after the operation and analysed for each patient. Results: Before treatment, the indices for the thickening of the subaxillary joint capsule, subacromial bursa (with or without effusion), long head of the biceps brachii tendon (LHBBT) and CHL were 40, 22, 16 and 14, respectively. After treatment, all the indices were significantly decreased (all P <0.010) except for that of the LHBBT (P =0.123). The patients’ CMSs improved, with the median total CMS increasing from 59 points (interquartile range: 53-64 points) to 86 points (interquartile range: 78-90 points) (P <.010). While the internal rotation (Ir) of the shoulder joint did not improve (FDRs <.50), abduction, forward flexion (Ff) and external rotation (Er) improved significantly (all FDRs =1.00). Conclusions: Compared with conservative treatment, US-guided intervention for FS in the frozen stage is highly effective and of great clinical value.